O pensamento teológico de Isac Alberto Rodrigues Aço na perspectiva de reino de Deus e missão : uma contribuição para a reflexão teológica e a prática pastoral da Igreja Metodista - Garin, Norberto da Cunha (2007)
The theological thinking of Aço, published in different printed media between 1964 and 1992, represents a contribution to the theological reflection and to the pastoral practices of the Methodist Church, considering the concepts of Kingdom of God and mission. Since his youth, his concern with justice and people s dignity has led him to fight for a Church directed toward the poor and sympathetic with the socially excluded. This thesis is presented in three chapters. The first covers biographical information, since Aço s birth in Angola, Africa, in 1935, until his tragic death in a car accident in 1991, focusing his missionary work developed in the agricultural schools of Angola and his effort to defy the Methodist Church to practice the Liberation Theology. The second chapter deals with his concept of God s Kingdom, in which there s room for all people emphasizing the place of the poor. The last chapter relates his concept of mission as a challenge to the Church to be simpathically envolved with the poor making them aware of their citizenship in this Kingdom.